RhD ‐negative red blood cell use and conservation strategies in the Region of Southern Denmark - Jochumsen, Emil Ainsworth; Titlestad, Kjell E.; Sprogøe, Ulrik; Yazer, Mark H. (Vox sanguinis, 2025)
Suboptimal use of RhD-negative red blood cells (RBCs) can lead to reduced inventories of this scarce resource. Prevention of D-alloimmunization is particularly important for RhD-negative females of childbearing potential (FCPs). The utilization of RBCs in the Region of Southern Denmark was analysed to elucidate opportunities for conserving RhD-negative RBCs. RBC transfusions from 1 January 2020 to 31 December 2024 were identified using the South Danish Transfusion Service's laboratory and inventory IT systems. RhD-typing results, including the time when the patient's RhD type became known, were used to identify whether a historical or current RhD type was available at the time of RBC transfusion. Transfusions were grouped into 72-h 'transfusion episodes', and the achievement of the RBC critical administration threshold (CAT; 3 RBC units/h) was noted. There were 30,564 recipients of 162,778 RBC units. Of these units, 36,483 (22%) units were RhD-negative, out of which 22,922 (63%) were crossmatched (i.e., sufficient time was available to demonstrate compatibility with recipient plasma) and issued to RhD-negative non-FCPs; 1934 (5%) units were uncrossmatched and urgently transfused to 1409 patients who were historically known to be RhD-positive, and 934 (3%) units were transfused to 303 non-FCPs without a current or historical RhD type. In RhD-negative patients who reached CAT, 1440 of 36,483 (4%) RhD-negative RBC units were transfused after they had reached CAT. Many of the RhD-negative RBC units were issued to recipients who were not RhD-negative FCPs, those known to be RhD-positive and those requiring massive transfusion, suggesting strategies for resource conservation.